2018
DOI: 10.1177/0840470418809105
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous model of care to health and social care workforce planning

Abstract: Indigenous people have always had the end in mind-a long range vision for the health and wellbeing of their families and communities. Creating Indigenous solutions-oriented approaches to strategic health and social care workforce planning is an essential component to the realization of self-determination and empowerment, accessible health services, community participation, and flexible approaches to care. This article suggests using an Indigenous "models of care" population health approach to health and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Researchers, community leaders, service providers, and decision-makers across the sectors gathered to build a shared vision for strengthening mental health services and programs for the region’s diverse Indigenous population. Participants envisioned a holistic and integrated mental health model that is Indigenous-led, culturally based, and blends western modalities with Indigenous knowledge and healing practices [ 24 , 68 ]. Given the importance of traditional healing practices and culturally appropriate care for Indigenous people, it is critical that these sources of healing are integrated into their care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers, community leaders, service providers, and decision-makers across the sectors gathered to build a shared vision for strengthening mental health services and programs for the region’s diverse Indigenous population. Participants envisioned a holistic and integrated mental health model that is Indigenous-led, culturally based, and blends western modalities with Indigenous knowledge and healing practices [ 24 , 68 ]. Given the importance of traditional healing practices and culturally appropriate care for Indigenous people, it is critical that these sources of healing are integrated into their care.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review found that mental health services developed by Indigenous communities in Canada were the most effective at providing appropriate care [ 19 ]. Co-creating Indigenous models of care with Indigenous communities has also been recommended to support self-determination, increased community participation in health, and increased community capacity [ 68 ]. Maar, Erskine [ 22 ] found that a collaborative, community-based Indigenous mental health care model led to improvements in culturally-safe care for Indigenous communities in northern Ontario, Canada [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research team, community leaders, service providers, and decision-makers came together to build a vision for improving mental health services and programs for the region's diverse Indigenous population. Participants envisioned a holistic and integrated mental health model that is Indigenous-informed and culturally-based, and grounded in community-led mental health and wellness services that blends Western modalities with Indigenous knowledge and healing practices (11,40). Given the importance of traditional healing practices and culturally appropriate care for Indigenous people, it is critical that these sources of healing are integrated into their care.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review (6) found that mental health services developed by Indigenous communities were the most effective at providing appropriate care. Co-creating Indigenous models of care with Indigenous communities has also been recommended to support self-determination, increased community participation in health, and increased community capacity (40). Maar, Erskine (9) found that a collaborative, community-based Indigenous mental health care model led to improvements in culturallysafe care for Indigenous communities in northern Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Our world has become no less surprising in the year since the publication of previous articles that suggested new approaches for combating healthcare system fragmentation and silo services. 10,36,52,54,64,65 Utilizing a population health and simulation approach at the community level will help all participants responsible for funding service outcomes to understand the demand for future resources, services, case mix, outcomes, and ongoing costs—leading to care models designed to address the needs of vulnerable people. 3,30,54,61,62,64,65,66…”
Section: Police and Mental Illness: Joining Up Servicesmentioning
confidence: 99%